Course and predictors of post‐traumatic stress disorder in a cohort of psychologically distressed patients with cancer: A 4‐year follow‐up study. Issue 2 (20th November 2017) - Chan, Caryn Mei Hsien; Ng, Chong Guan; Taib, Nur Aishah; Wee, Lei Hum; Krupat, Edward; Meyer, Fremonta
Abstract : BACKGROUND: Scant evidence exists on the long‐term course of cancer‐related post‐traumatic stress disorder (PTSD). This is among the few studies worldwide, and the first in the South‐East Asian region, to prospectively evaluate PTSD in patients with cancer using gold‐standard clinical interviews. The objective of the study was to assess the course and predictors of PTSD in adult patients with cancer in a South‐East Asian population. METHODS: A prospective, longitudinal study was conducted in a cohort of 469 consecutively recruited patients (aged ≥18 years) with various cancer types within 1 month of diagnosis at a single oncology referral center. Only patients who had significant psychological distress (Hospital Anxiety and Depression Scale total cutoff score ≥16) underwent the PTSD module of the Structured Clinical Interview for the Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition, Text Revision (SCID) at at 6‐months follow‐up. All patients completed the SCID at the 4‐year follow‐up assessment regardless of their initial Hospital Anxiety and Depression Scale score. RESULTS: In an analysis combining patients who had both full and subsyndromal PTSD, there was a 21.7% incidence of PTSD at the 6‐month follow‐up assessment (n = 44 of 203 SCID‐interviewed patients), with rates dropping to 6.1% at the 4‐year follow‐up assessment (n = 15 of 245 SCID‐interviewed patients). Patients with breast cancer (compared with those who had other types of cancer) were 3.68 times less likely to develop PTSD at 6‐months, but not at 4‐years follow‐up. CONCLUSIONS: The overall rates of PTSD decreased with time, but one‐third of patients (34.1%) who were initially diagnosed had persistent or worsening PTSD 4 years later. There is a need for early identification of this subset of patients who have cancer with PTSD to design risk‐targeted interventions. Cancer 2018;124:406‐16 . © 2017 American Cancer Society . Abstract : This is among the few studies worldwide, and the first in the South‐East Asian region, to prospectively evaluate post‐traumatic stress disorder using gold‐standard clinical interviews in a 4‐year follow‐up cohort of patients with cancer. The results indicate that Asian patients with cancer may be at higher risk of developing post‐traumatic stress disorder within the first 6 months of diagnosis and treatment.